Innovation and Inter-Organisational Linkages in Malaysian Machinery and Equipment Sector : A Review Using Innovation System Perspectives - Parvardeh, Hossein (2013)
The Malaysian machinery and equipment sector is very diverse, involving SMEs, MNCs, Local firms, and subsidiaries of foreign firms. Malaysian government intends to push the sector up the value chain; however, the sector does not feature in research studies related to innovation. The present study aims at finding the main drivers of innovation in this sector along with depicting the main features of National Innovation systems in Machinery and equipment sector in Malaysia. The main focus has been placed on the linkages that the firms develop in the ecosystem they are operating. A case-study approach was employed to further investigate into the above mentioned issues. Data collection was conducted through various methods, such as in-depth interviews with numerous key managers and personnel in this sector. Overall, the findings from the cases indicate a few number of innovation capability developments in small enterprises and also large foreign firms. The strongest links are with customers and suppliers and it can be said that there is very minimal or almost nonexistence of any interaction with universities or research institutions. Development of innovation capacity is being driven essentially from internal motivations or with strong linkages to customers and/or suppliers. There appears to be no strong sectorial innovation system for supporting development of innovation capabilities and also there is no interest / awareness by the firms about developing linkages to different actors or institutions. Based on the indicative conclusions, some policy implications are presented.